2021
DOI: 10.1142/s0218127421500474
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Hidden Dynamics and Multistability of a Class of Two-Dimensional Maps via Linear Augmentation

Abstract: This paper reports the complex dynamics of a class of two-dimensional maps containing hidden attractors via linear augmentation. Firstly, the method of linear augmentation for continuous dynamical systems is generalized to discrete dynamical systems. Then three cases of a class of two-dimensional maps that exhibit hidden dynamics, the maps with no fixed point and the maps with one stable fixed point, are studied. Our numerical simulations show the effectiveness of the linear augmentation method. As the couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In this section, the dynamical behaviors of the rational map (1) will be investigated in five cases in accordance with different types of fixed points. In each case, the random bifurcation diagram [30] is drawn firstly to show the possible attractors of the rational map (1). If no multi-stability is observed, the forward (backward) bifurcation diagram will be presented to show the complex behaviors of the rational map (1).…”
Section: Dynamical Behaviors Of the Rational Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, the dynamical behaviors of the rational map (1) will be investigated in five cases in accordance with different types of fixed points. In each case, the random bifurcation diagram [30] is drawn firstly to show the possible attractors of the rational map (1). If no multi-stability is observed, the forward (backward) bifurcation diagram will be presented to show the complex behaviors of the rational map (1).…”
Section: Dynamical Behaviors Of the Rational Mapmentioning
confidence: 99%
“…[21]. Great efforts [26][27][28][29][30] have also been made for searching and controlling hidden attractors. For example, Dudkowski et al [26,27] presented a new method to locate hidden and coexisting attractors in non-linear maps based on the concept of perpetual points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-stability and extreme multi-stability of dynamical systems have been found in many disciplines, including physics, chemistry, biology, and economics. [35,36] Very recently, extreme multi-stability of nonlinear maps has received much attention. [37][38][39][40] In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also shown that the existing LA control for flows can be extended to discrete dynamical systems as well. In this context, Zhang et al [41] applied this generalized control strategy to various classes of maps, for example, the one exhibiting hidden dynamics, no fixed points and the ones exhibiting one stable fixed point.…”
mentioning
confidence: 99%